PTH-015 Low risk adenomas with villous component resected at bowel scope – outcomes at colonoscopy. (17th June 2017) - Elzubeir, A; Verma, AM
Abstract : Introduction: Adenomas detected at Bowel Scope are classified based on the BSG guideline on adenoma follow up. Subjects with high or intermediate risk adenomas are referred for colonoscopy to clear the whole colon of polyps. Subjects with low risk adenomas (one or two sub 1 cm adenomas) undergo polypectomy and are discharged. However, in deviation to the guideline, if adenomas have villous component – tubulovillous adenoma (TVA) or villous adenoma (VA), they are upstaged to intermediate risk and subjects are referred for colonoscopy. We audit the outcome of the colonoscopies in subjects who have been upstaged. Method: Interrogating the Northamptonshire Bowel Scope database, subjects with upstaged adenomas were identified. Colonoscopy and histology reports were reviewed, data collated and analysed. This covered a time period from July 2014 to February 2017 (6000+ Bowel Scope procedures have been performed). Results: 64 subjects ( 1% of Bowel Scope subjects) had upstaged adenomas. 47 males (73.4%) and 17 females (26.6%), 60 TVAs and 4 VAs. 58 subjects had 1 adenoma, six had 2 adenomas. Two subjects had 2 adenomas with villous component (1 had two TVAs with high grade dysplasia). 66 TVAs/VAs in total, mean and median size=6 mm. 24 in rectum (36.4%), 35 in sigmoid colon (53.0%), 7 in descending colon (10.6%). 6 subjects have not had colonoscopy (9.4%) - 4 (male) subjects declined, 2 subjects awaiting colonoscopy. 36 (56.3%) had no further adenomas seen at colonoscopy (2 hyperplastic polyps). 22/64 (34.4%) subjects had further adenomas – 17 males (81.0%), 4 females (19.0%). 14 single adenomas, 3 multiple, 1 serrated adenoma (SSA) and 4 non-retrieved. 27 adenomas resected, 23 diminutive (sub 5 mm, 20 TAs, 2 TVAs, 1 SSA). 4 larger adenomas; 9 mm, 9 mm, 12 mm and 20 mm (all TVAs). After colonoscopy, 54/58 (93.1%) patients classed as low risk, 1 (1.7%) as intermediate risk and 3 (5.2%) as high risk. Conclusion: 66 subjects with low risk adenomas at Bowel Scope upstaged due to villous component yielded 58 colonoscopies thus far (90.6% of eligible) with an overall polyp detection rate of 39.7% and adenoma detection rate of 31.0%. There is a male predominance, 56.3% yielded no adenomas. 85.2% of adenomas resected are diminutive. Only 4 (male) subjects remain upstaged after colonoscopy to intermediate or high risk groups (6.1%). This data opens up a debate to whether upstaging subjects found to have low risk adenomas with villous component is an effective strategy. 93.9% of subjects end up classed as low risk after colonoscopy and the vast majority of adenomas resected at colonoscopy are diminutive. The number needed to colonoscope to remain upstaged is 14.5. Reference: . SR Cairns, JH Scholefield, RJ Steele, et al. Guidelines for colorectal cancer screening and surveillance in moderate and high risk groups (update from 2002). Gut2010;59:666–690. Disclosure of Interest: None Declared